A multi-center, randomized, double-blinded, parallel, placebo-controlled study to assess the efficacy and safety of Shenqisuxin granule in complex coronary artery disease after PCI: Study protocol - Wu, Xiaoping; Yan, Mingyu; Pang, Xingxue; Wu, Hui; Hu, Zhigeng; Xiao, Rui; Pan, Jianlue; Li, Ying; Shi, Shengnan; Deng, Yanping; Li, Jiaxi; Wang, Peili; et al. (Frontiers in Cardiovascular Medicine, 2022)
Introduction: The Shenqisuxin granule (SQSX), a novel Chinese herbal formula, has the effect of preventing in-stent restenosis and improving angiogenesis. We intend to evaluate the efficacy and safety of SQSX to provide a possible therapeutic strategy for complex coronary artery disease (CCAD) after percutaneous coronary intervention (PCI). Methods/Design: The study is a multi-center, randomized, double-blinded, parallel, placebo-controlled trial. A total of 120 participants will be randomized 1:1 into the intervention group and the control group. Based on standardized treatment, the intervention group and control group will receive SQSX and placebo for 2 months, respectively. The primary outcomes, metabolic equivalents (METS) and peak oxygen uptake (Peak VO2), and the secondary outcomes, including other indicators of cardiorespiratory fitness (CRF), the European Quality of Life Questionnaire (EQ-5D-5L), the Seattle Angina Scale (SAQ), etc., will be assessed at baseline and 2 months ± 3 days. In addition, the survey scales will also be tested at 1 month ± 3 days. Trimethylamine N-oxide (TMAO), high-sensitivity C-reactive protein (hs-CRP), and gut microbiota features will be assessed at baseline and 2 months ± 3 days to probe possible mechanism. The major adverse cardiac and cerebrovascular events (MACCE) and bleeding events will be monitored until the 12-month follow-up. Discussion: This study is launched to assess the efficacy and safety of SQSX in CCAD after PCI and probe the possible mechanism. Trial Registration: China Clinical Trial Registry, ChiCTR2200060979. Registered on June 14, 2022.